Meningkatkan Kemampuan Guru Melalui Pemberdayaan MGMP Sekolah di Madrasah Aliyah Negeri 1 Barru - ahmad ahmad (Universitas Negeri Makassar, 2019)
This study aims to determine the increase in teacher capacity through the school MGMP. School action research method (PTS) with two cycles in which each cycle consists of stages (1) planning, (2) implementation of corrective actions, (3) observation, and (4) reflection. This study involved 13 Mathematics and Natural Sciences teachers as research subjects. The results of the study showed that (a) there was an increase in the ability of teachers of State Madrasah Aliyah through school MGMP. This can be seen from the results of observations in two cycles, also in the results of the tests conducted, it was seen that the increase in posttest test results was significantly. In the distribution of questionnaires conducted to determine teacher perceptions / opinions about school MGMP, the questionnaire results were at 85%, so the teacher benefited directly from MGMP schools to improve their abilities. Based on the results of this study the authors recommend to MGMP school participants teachers: (1) Utilizing school MGMP activities as a forum for empowerment to